Bayesian semi-parametric spatial modelling of intimate partner violence in Namibia using 2013 Demographic Health Survey Data - Oludoyinmola Ojifinni; Innocent Maposa; Latifat Ibisomi (BMC, 2021)
Abstract Background Intimate partner violence (IPV) is an important public health problem with health and socioeconomic consequences and is endemic in Namibia. Studies assessing risk factors for IPV often use logistic and Poisson regression without geographical location information and spatial effects. We used a Bayesian spatial semi-parametric regression model to determine the risk factors for IPV in Namibia; assess the non-linear effects of age difference between partners and determine spatial effects in the different regions on IPV prevalence. Methods We used the couples' dataset of the 2013-2014 Namibia Demographic and Health Survey (DHS) obtained on request from Measure DHS. The DHS domestic violence module included 2226 women. We generated a binary variable measuring IPV from the questions "ever experienced physical, sexual or emotional violence?" Covariates included respondent's educational level, age, couples' age difference, place of residence and partner's educational level. All estimation was done with the full Bayesian approach using R version 3.5.2 implementing the R2BayesX package. Results IPV country prevalence was 33.3% (95% CI = 30.1-36.5%); Kavango had the highest [50.6% (95% CI = 41.2-60.1%)] and Oshana the lowest [11.5% (95% CI = 3.2-19.9%)] regional prevalence. IPV prevalence was highest among teenagers [60.8% (95% CI = 36.9-84.7%)]). The spatial semi-parametric model used for adjusted results controlled for regional spatial effects, respondent's age, age difference, respondent's years of education, residence, wealth, and education levels. Women with higher education were 50% less likely to experience IPV [aOR: 0.46, 95% CI = 0.23-0.87]. For non-linear effects, the risk of IPV was high for women ≥ 5 years older or ≥ 25 years younger than their partners. Younger and older women had higher risks of IPV than those between 25 and 45 years. For spatial variation of IPV prevalence, northern regions had low spatial effects while western regions had very high spatial effects. Conclusion The prevalence of IPV among Namibia women was high especially among teenagers, with higher educational levels being protective. The risk of IPV was lower in rural than urban areas and higher with wide partner age differences. Interventions and policies for IPV prevention in Namibia are needed for couples with wide age differences as well as for younger women, women with lower educational attainment and in urban and western regions.